The Dynamics of Kafa’ah Nasab and the Identity of Sharifah Women: An Examination of Sayyid Utsman's Perspectives within the Context of Gender Equality - Ahmad Azzam Nouvaldi; Mohammad Syifa Amin Widigdo (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam)
This research discusses concepts kafa'ah nasab in marriage, especially in the family community of habaib descendants (sayyid and syarifah), which is examined through the perspective of Sayyid Utsman bin Yahya's thoughts and reviewed within the framework of gender equality and Islamic sociological studies. In the habaib tradition, marriage between a syarifah and a non-sayyid man is often rejected on the basis of lack of lineage, and is even considered to violate social and religious norms. Sayyid Uthman, as one of the great scholars of the Dutch East Indies colonial period, emphasized the invalidity of this marriage in several of his works, which later became an important reference in the social structure of the habaib. However, from the perspective of gender equality, this practice raises the problem of discrimination against women and strengthens the patriarchal system based on lineage. This research uses a qualitative approach using literature study methods and interviews with Rabithah Alawiyah. The research results show that kafa'ah nasab in practice it has turned into a social control mechanism that limits women's freedom in choosing a life partner, and creates inequality in gender relations. Therefore, a reinterpretation of this concept is needed so that it is in line with Islamic sociology and the principles of justice in Islam.